2020
DOI: 10.1021/acs.langmuir.0c02595
|View full text |Cite
|
Sign up to set email alerts
|

Pickering Emulsifiers Based on Block Copolymer Nanoparticles Prepared by Polymerization-Induced Self-Assembly

Abstract: Block copolymer nanoparticles prepared via polymerization-induced self-assembly (PISA) represent an emerging class of organic Pickering emulsifiers. Such nanoparticles are readily prepared by chain-extending a soluble homopolymer precursor using a carefully selected second monomer that forms an insoluble block in the chosen solvent. As the second block grows, it undergoes phase separation that drives in situ self-assembly to form sterically stabilized nanoparticles. Conducting such PISA syntheses in aqueous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 241 publications
(605 reference statements)
0
41
0
Order By: Relevance
“… 306 For more details on Pickering emulsifier application of PISA-prepared nanoparticles, the reader is referred to a recent review for good insight. 309 …”
Section: Applicationsmentioning
confidence: 99%
“… 306 For more details on Pickering emulsifier application of PISA-prepared nanoparticles, the reader is referred to a recent review for good insight. 309 …”
Section: Applicationsmentioning
confidence: 99%
“…However, good dispersibility and sustained sunscreen-release property have been two main challenges for the design of efficient nanocapsules. It has been reported that most of the sunscreen nanocapsules had poor dispersibility in emulsion [ 10 ], limiting their application in sunscreen products. The way of layer-by-layer self-assembly (LBL) was a new strategy to prepare the nanocapsules with nano-size and good dispersibility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the hydrophilicity of the PISA‐synthesized polymeric particles on emulsion was discovered by Armes and coworkers. [ 97 ] Changing the hydrophilicity or hydrophobicity would lead to an increase in the solubility of particles in the aqueous or oil phase, so the particles tend to dissolve in one phase, leading to demulsification. As discussed in Section 2, the pH‐responsive and CO 2 ‐responsive emulsions are mainly achieved by increasing their hydrophilicity under the addition of acid or CO 2 gas.…”
Section: Factors That Influence Pickering Emulsion Dropletsmentioning
confidence: 99%